Sacred groves in conservation of plant biodiversity in Banaskantha district, Gujarat, India. - Patel, P K; Patel, M K (Recent Research in Science and Technology, 2013)
Nature conservation practices are very ancient tradition in India. Useful biodiversity species have much reverence in culture of our country. Sacred groves are seen through out Gujarat, having varied forms, cultural practices and belief systems. The vegetation in the groves is highly varied viz. mangroves, fresh water swamps, or other tropical forest types. Sacred groves represent long tradition of environmental conservation based on indigenous knowledge by the tribal communities of Banaskantha District, Gujarat, India. The study deals with the role of sacred groves in conservation of plant biodiversity in Banaskantha District, Gujarat, India. Among the 11 sacred groves surveyed, over 25 different plant species are reported. In the sacred groves surveyed, only a few are well protected while most are partially threatened due to anthropogenic pressure. Considering all the dimensions of sacred groves, it is clear that these groves are considered as one of the most species-rich areas for plants, birds and mammals.